2018
DOI: 10.1007/s10623-018-0499-9
|View full text |Cite
|
Sign up to set email alerts
|

Covers and partial transversals of Latin squares

Abstract: We define a cover of a Latin square to be a set of entries that includes at least one representative of each row, column and symbol. A cover is minimal if it does not contain any smaller cover. A partial transversal is a set of entries that includes at most one representative of each row, column and symbol. A partial transversal is maximal if it is not contained in any larger partial transversal. We explore the relationship between covers and partial transversals. We prove the following: (1) The minimum size o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…The same problem for Latin squares [15] is yet to be resolved. The current best answer to "how close we can get" to a transversal in a Latin square is by Keevash, Pokrovskiy, Sudakov and Yepremyan [23], improving older results by Hatami and Shor [21,28] (see also [6]); similar questions arise for the aforementioned generalized transversals, which is a possible future research direction.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The same problem for Latin squares [15] is yet to be resolved. The current best answer to "how close we can get" to a transversal in a Latin square is by Keevash, Pokrovskiy, Sudakov and Yepremyan [23], improving older results by Hatami and Shor [21,28] (see also [6]); similar questions arise for the aforementioned generalized transversals, which is a possible future research direction.…”
Section: Discussionmentioning
confidence: 94%
“…Along these lines, the existence of a Latin square that decomposes into d × (n/d) submatrices containing all n symbols was resolved in [11]: it is possible for all divisors d of n. In [6], the authors observe that all Latin squares of order n have an O(n 1/2+ε ) × O(n 1/2+ε ) submatrix containing n−O(n 1/2+ε ) distinct symbols, which raised the existence problem for Latin squares of order n 2 which cannot decompose into n × n submatrices which contain all n symbols.…”
Section: Discussionmentioning
confidence: 99%
“…It is not hard to see that a maximal partial transversal of length ℓ in a Latin square of order n must satisfy n n 2 ∕ ⩽ ℓ ⩽ . In [6] it was shown that for n 5 ⩾ all values of ℓ in this range are achieved. Then Evans [14] constructed an infinite family of Latin squares which simultaneously have maximal partial transversals of each of the permissible lengths.…”
Section: Every M Nmentioning
confidence: 95%
“…Proof. In [12], it was shown that there exists a partial transversal of cardinality n − O log n log log n , and [3] it was shown that a partial transversal of cardinality n − d can be used to construct a cover of cardinality n + d/2. Therefore, there exists a cover of cardinality n + O log n log log n in L. The proof now follows from Theorem 4.2.…”
Section: Localization Number Of Latin Squaresmentioning
confidence: 99%